Time-dependent formulations for minimizing total completion time in a parallel machine scheduling problem with dependent setup times. Issue 12 (2016) - Baez, Sarahi; Angel-Bello, Francisco; Alvarez, Ada
Abstract: In this work two formulations for minimizing the total completion time a parallel machine scheduling problem with dependent set up times are proposed. They are developed from formulations for the same problem for a single machine environment and showed have a better performance than a formulation based on m-Traveling Salesmen Problem, consuming less computational time on instances of the same size and allow solving to optimality more than five times larger data instances.